The Value of Contrast-Enhanced Magnetic Resonance Imaging Enhancement in the Differential Diagnosis of Hepatocellular Carcinoma and Combined Hepatocellular Cholangiocarinoma. (15th September 2022) - Lu, Lun; Zhang, ChenCai; Yu, Xian; Zhang, Ling; Feng, YaYuan; Wu, YuXian; Xia, JinJu; Chen, Xue; Zhang, RuiPing; Zhang, Juan; Jia, Ningyang; Zhang, SiSi
Abstract : Background . The distinction between combined hepatocellular-cholangiocarcinoma (cHCC-CC) and hepatocellular carcinoma (HCC) before the operation has an important clinical significance for optimizing the treatment plan and predicting the prognosis of patients. Magnetic resonance imaging (MRI) has been widely used in the preoperative diagnosis and evaluation of primary liver malignant tumors. Purpose . The aim is to study the value of preoperative clinical data and enhanced MRI in the differential diagnosis of HCC and cHCC-CC and obtain independent risk factors for predicting cHCC-CC. Study type . Retrospective. Population. The clinical and imaging data of 157 HCC and 59 cHCC-CC patients confirmed by pathology were collected. Field Strength/Sequence . 1.5T; cross-sectional T1WI (gradient double echo sequence); cross-sectional T2WI (fast spin echo sequence, fat suppression); enhancement (3D LAVA technology). Assessment . The differences between the HCC and cHCC-CC patients were compared. Statistic Tests . Using the t -test, chi-square test, and logistic regression analysis, P < 0.05 was considered statistically significant. Result . 1. CHCC-CC was more likely to show multiple lesions than HCC (28.81% vs. 10.83%, P = 0.001 ) and more prone to microvascular invasion (MVI) (36.31% vs. 61.02%, P < 0.001 ). However, HCC had a higher incidence of liver cirrhosis than cHCC-CC (50.85% vs. 72.61%, P = 0.003 ). 2. The incidence of nonsmooth margin was higher in the cHCC-CC group (84.75% vs. 52.23%, P < 0.001 ). The incidence of peritumor enhancement in the arterial phase was higher in the cHCC-CC group (11.46% vs. 62.71%, P < 0.001 ) 3. According to the multivariate analysis, arterial peritumor enhancement (OR = 8.833, 95%CI:4.033, 19.346, P < 0.001 ) was an independent risk factor for cHCC-CC (P < 0.001 )). It had high sensitivity (62.71%) and specificity (88.54%) in the diagnosis of cHCC-CC. Date Conclusions . Liver cirrhosis and the imaging findings of GD-DTPA-enhanced MRI are helpful for the differential diagnosis of HCC and cHCC-CC. In addition, the imaging sign of peritumoral enhancement in the arterial phase has high sensitivity and specificity for the diagnosis of cHCC-CC.